Center of pressure responses to unpredictable external perturbations indicate low accuracy in predicting fall risk in people with Parkinson’s disease - Moraca, Gabriel Antonio Gazziero [UNESP]; Beretta, Victor Spiandor [UNESP]; Santos, Paulo Cezar Rocha dos [UNESP]; Nóbrega-Sousa, Priscila [UNESP]; Orcioli-Silva, Diego [UNESP]; Vitório, Rodrigo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Wiley, 2021)
Falls are associated with impairment in postural control in people with Parkinson's disease (PwPD). We aimed to predict the fall risk through models combining postural responses with clinical and cognitive measures. Also, we compared the center of pressure (CoP) between PwPD fallers and non-fallers after unpredictable external perturbations. We expected that CoP parameters combined with clinical and cognitive measures would predict fall risk. Seventy-five individuals participated in the study. CoP parameters were measured during postural responses through five trials with unpredictable translations of the support-surface in posterior direction. Range and peak of CoP were analyzed in two periods: early and late responses. Time to peak (negative peak) and recovery time were analyzed regardless of the periods. Models included the CoP parameters in early (model 1), late responses (model 2), and temporal parameters (model 3). Clinical and cognitive measures were entered into all models. Twenty-nine participants fell at least once, and 46 PwPD did not fall during 12 months following the postural assessment. Range of CoP in late responses was associated with fall risk (p = .046). However, although statistically non-significant, this parameter indicated low accuracy in predicting fall risk (area under the curve = 0.58). Fallers presented a higher range of CoP in early responses than non-fallers (p = .033). In conclusion, although an association was observed between fall risk and range of CoP in late responses, this parameter indicated low accuracy in predicting fall risk in PwPD. Also, fallers demonstrate worse postural control during early responses after external perturbations than non-fallers, measured by CoP parameters.
Keywords: Doença de Parkinson; Pressão; Equilíbrio postural; Distúrbios do movimento; Center of pressure; Movement disorders; Support-surface translation; Postural control; Falls prediction